An experimental study on the yellow cosmos (C.Sulphureus) as a potential dye source for textiles - Menez, Vanessa Jane F.
Despite the advantage and preferred use of synthetic dyes today, the study of natural dyes finds relevance through the knowledge gained from the basic methods in dyeing textiles which promotes better understanding and appreciation of the coloring process. Among the studies done on natural dyes, those taken from flowers are among the least explored. The cosmos plant has graceful flowers which are usually yellow, orange or pink. The study explores the possibility of extracting from the flower heads of the yellow cosmos (C. Sulphureus) a dye suitable for textiles. It aims to understand some of the dyeing properties of the yellow cosmos and find an effective procedure for extraction and fabric dyeing. The study would try to determine the optimum color that could be exhausted from the flower heads and to utilize this as basis for the dye concentration to be used in the dyeing procedure. It would also consider the maximum shelf life of the dye extract. Included in the procedure to be utilized are the identification of the best mordant percentages of the mordanting agents and of the dye concentration. Finally the resulting dyed fabrics are subjected to testing for colorfastness to light and washing to determine its practicality to everyday use. In reviewing the related literature, the potentiality of the yellow cosmos as source of natural dye was discussed. There appears to be a greater possibility in obtaining a dye from the cosmos flowers because of its identification as a composite flower. majority of known floral dye sources comes from the composite family. Furthermore, a stain was easily obtained from the flower heads upon crusing which when done on other flowers did not produce a color of stain. This was a preliminary test suggested by Eunice Svinicki in ascertaining the potentiality of a material as dye source. From here, the methods used by the known composite flowers were analyzed, together with other methods used by non-composite flowers. The data gathered from these and from the studies made on natural dyes fairly established the study's methodology. Among the studies were: Talahib Grass (Saccharum Spontaneum, Ann): A Study of its Potential as a Source of Natural Dye (Lachica, M.E.), A Pilot Study on the Utilization of the Leaves of the Mayana (Coleus blumei, Benth) as a Potential Source of Natural Dye for Textiles (Gallo, L.). A study on the Dyeing Properties of Sibukao Wood Extract (Llamas, E. & Tayag, C), and A Study on the Acid-Base Indicators Found on the Coloring Matter of Some Plants (Velasco, J.). The review also discussed fundamentals in dyeing and on the theory of dyeing. This is to better understand the behavior of dye and fiber upon dyeing and more importantly to understand the significance of the processes involved in dyeing procedure. Finally, the process involved in the testing of the resulting dyed fabrics to colorfastness to light and washing was discussed. The study performed several experiments, such as (1) dye extraction by soaking, pulverizing/blending, chopping and cutting using water as solvent, (2) observing the colors exhausted from the flower heads at different water-dyestuff percentage from (25%-275%), (3) mordanting of selected fabrics at 3%-12% mordanting agents: alum-cream of tartar and alum-tannin, (4) dyeing of fabrics at the selected dye concentration, (5) dyeing of stored dye extracts to determine its acceptable shelf life, (6) and testing of the best resulting dyed fabric for colorfastness to light and washing. The fabrics tested consisted of cotton, silk, linen and spun twill (blend fabric of polyester-cotton). The procedure involved does not greatly deviate from general procedures used on other natural sources. Fabrics were pretreated, then mordanted, and finally dyed from the dye extract taken from the dyestuff. Dependent variables were the mordant and dye percentages used. While dyeing temperature and time, liquor ration (1:30), and solvent used were kept constant. The dyestuff used were gathered from different locations. Thus, the experiments were done by batches according to the place where they were gathered. The study was able to find the yellow cosmos to be a valuable source of natural dye. A dye can be extracted from the flower heads of the yellow cosmos plant. Moreover, the obtained dye could evenly color the selected fabrics, especially the silk and spun twill fabrics. Silk and spun twill mordanted at 8% alum-tannin and 10% alum-cream of tartar using 100% 150% dye concentration exhibited the most satisfactory results. A general rating of 1.5 for colorfastness to laundering according to its degree of alteration in lightness, hue and saturation of colors was given. This indicates change in color. Only the silk fabric mordanted at 8% alum-tannin produced a higher rating of 3.5, which indicates just a noticeable change in color. Tests on the fabrics' degree of staining showed a rating of 4.5 which indicates negligible staining. Test conducted on the fabrics' colorfastness to light showed a high rating of 3.0 to 4.0 for the silk fabrics. While spun twill exhibited poor fastness to light, demonstrating much change in color. The study found that at 200% or at 4:1 ratio of water to dyestuff resulted to a stable color. The dye extracts minimum shelf life remains inconclusive. It was found that there were too many factors that may have contributed to the differences in behavior of the stored dye extracts.